A Machine Learning Framework for Discriminating between ChatGPT and Web Search Results - Iqbal, Md. Sadiq; Kashem, Mohammod Abul; Chowdhury, Mohammad Asaduzzaman (Statistics, Optimization & Information Computing, 2025)
ChatGPT is a large language model built by OpeanAI. It is based on an architecture called the Generative pre-trained transformer (GPT). It can generate text that appears to be written by a human and understands natural language questions. We want to investigate whether we can distinguish between query results from web search and ChatGPT by utilizing Machine learning (ML). To accomplish the investigation this research trains five different Machine learning (ML) methods on a balanced dataset containing 2010 samples of query results from ChatGPT and web search. These ML models are Random forest (RF), Naive Bayes (NB), Decision tree (DT), Support vector machine (SVM), and Logistic regression (LR). Each of these methods is experimented with two feature optimization techniques namely LDA and PCA. After analyzing the results of all experiments, it is determined that the combination of NB with LDA yields the highest accuracy of 99.75%. Besides this technique also identifies ChatGPT-generated and human-written text with an accuracy of 98.67 from an existing dataset, and this outcome outperforms the state-of-the-art (SOTA) techniques. However, the proposed intelligent approach will help to identify any text of ChatGPT.